2014
DOI: 10.1371/journal.pone.0113712
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Oxidative DNA Damage and Altered DNA Methylation in the BTBR T+tf/J Mouse Model of Autism and Similarities with Human Post Mortem Cerebellum

Abstract: The molecular pathogenesis of autism is complex and involves numerous genomic, epigenomic, proteomic, metabolic, and physiological alterations. Elucidating and understanding the molecular processes underlying the pathogenesis of autism is critical for effective clinical management and prevention of this disorder. The goal of this study is to investigate key molecular alterations postulated to play a role in autism and their role in the pathophysiology of autism. In this study we demonstrate that DNA isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 57 publications
2
81
0
Order By: Relevance
“…Elevated levels of 8-oxo-7-hydrodeoxyguanosine, [8-oxodG] the most studied oxidative DNA lesion and an oxidative stress marker, and increased 5-methylcytosine [5mC] were associated with reduced expression of the 8-oxoguanine DNA-glycosylase 1 [ Ogg1 ]; and increased expression of de novo DNA methyltransferases 3a and 3b [ Dnmt3a and Dnmt3b ]. Similar changes were observed for human postmortem analysis of cerebellar epigenetic changes in ASD patients (Shpyleva et al, 2014). …”
Section: Altered Gene and Protein Expression In The Btbr Mousesupporting
confidence: 81%
See 1 more Smart Citation
“…Elevated levels of 8-oxo-7-hydrodeoxyguanosine, [8-oxodG] the most studied oxidative DNA lesion and an oxidative stress marker, and increased 5-methylcytosine [5mC] were associated with reduced expression of the 8-oxoguanine DNA-glycosylase 1 [ Ogg1 ]; and increased expression of de novo DNA methyltransferases 3a and 3b [ Dnmt3a and Dnmt3b ]. Similar changes were observed for human postmortem analysis of cerebellar epigenetic changes in ASD patients (Shpyleva et al, 2014). …”
Section: Altered Gene and Protein Expression In The Btbr Mousesupporting
confidence: 81%
“…Apart from the differential gene expression patterns, BTBR mice exhibit increased epigenetic alterations to the DNA in the cerebellum (Shpyleva et al 2014). Elevated levels of 8-oxo-7-hydrodeoxyguanosine, [8-oxodG] the most studied oxidative DNA lesion and an oxidative stress marker, and increased 5-methylcytosine [5mC] were associated with reduced expression of the 8-oxoguanine DNA-glycosylase 1 [ Ogg1 ]; and increased expression of de novo DNA methyltransferases 3a and 3b [ Dnmt3a and Dnmt3b ].…”
Section: Altered Gene and Protein Expression In The Btbr Mousementioning
confidence: 99%
“…The over‐expression of 8‐oxoguanine DNA glycosylase (OGG1) is the hallmark of the normal brain aging (Lu et al, ). It is reported that the interaction between OGG1 and X‐ray repair cross complementing 1 has been implicated in schizophrenia (Derakhshandeh, Saadat, Farrashbandi, & Saadat, ; Odemis et al, ; Psimadas et al, ; Saadat, Pakyari, & Farrashbandi, ) and autism spectrum disorder (Shpyleva et al, ; Xu, Rosales‐Reynoso, Barros‐Nunez, & Peprah, ; Young, McKinney, Ross, Wahle, & Boyle, ). It is found that the expression of OGG1 is increased in white matter oligodendrocytes of patients with MDD (Szebeni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that an increase in oxidative stress, and 8‐oxoG in particular, has been implicated in many diseases, including autism (Shpyleva et al, ), Alzheimer's disease (Hofer & Perry, ; Isobe, Abe, & Terayama, ), Parkinson's disease (Kikuchi et al, ), epilepsy (RumiĂ  et al, ), multiple system atrophy (MSA; Kikuchi et al, ), dementia with Lewy bodies (Lyras et al, ), and ALS; Chang et al, ) and FASD (Brocardo et al, ; Miller‐Pinsler et al, ; Patten et al, ). Interestingly, children with FASD demonstrate comorbidity with autism (Landgren, Svensson, Strömland, & Andersson Grönlund, ; Mukherjee, Layton, & Yacoub, ) and other phenotypes including abnormal peripheral nervous system disorder, conduct disorder, receptive language disorder, chronic serous otitis media, and expressive language disorder (Popova et al, ).…”
Section: Comorbidity Of Fasd and Other Diseases Involving Oxidative Smentioning
confidence: 99%